Hubungan Adekuasi Hemodialisa Dengan Stres, Kecemasan, dan Depresi Pada Pasien Yang Menjalani Hemodialisis di RSUD Praya Lombok Tengah - Paoh, Kharisma Alsyad Nur Azizah; Syuhada, Irwan; Rahadianti, Dian; Fatrahady, Lalu Buly (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the relationship between hemodialysis adequacy and the levels of stress, anxiety, and depression among patients undergoing hemodialysis at RSUD Praya Lombok Tengah. The study employed an analytical observational design with a cross-sectional approach. The sample was drawn from patients undergoing routine hemodialysis therapy. Data were collected using the validated Depression, Anxiety, and Stress Scale 42 (DASS-42) questionnaire. Data analysis was conducted using the chi-square statistical test. If the assumptions for the chi-square test were not met, the Kendall Tau test was applied. The study revealed a significant relationship between hemodialysis adequacy and levels of stress (p < 0.001; r = 0.627), anxiety (p < 0.001; r = 0.518), and depression (p < 0.05; r = 0.612) among patients. Hemodialysis adequacy is associated with levels of stress, anxiety, and depression in patients undergoing hemodialysis therapy. These findings highlight the importance of ensuring hemodialysis adequacy to support the psychological well-being of patients.